A PROSPECTIVE STUDY ON ANTIMICROBIAL UTILIZATION PATTERN IN OUTPATIENT DEPARTMENT AT TERTIARY CARE HOSPITAL, PUNE, INDIA. - Deshmukh, Sarang A; Agarwal, Yashasvi; Hiran, Harshita; Bhosale, Uma (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of the study was to evaluate antimicrobial prescription pattern in outpatient departments. Method: This was a prospective, cross-sectional and observational study over 12 weeks total 400 prescriptions of either gender and age; containing antimicrobial agents (AMAs) were analyzed for demographic data and the WHO prescribing indicators. Results: Most of prescription were given to men (n=262). The most common group of AMA used was Cephalosporins (n=141, 35.25%); of which Ceftriaxone was most commonly prescribed (n=73, 18.25%). 10 AMAs were from the WHO essential medicine list AMAs. Men outnumbered women in prescribing antibiotics (n=262 vs. 138). Most of AMAs receivers were between 26 and 35 years (n=128, 32%). Amoxicillin+Clavulanic acid fixed-dose combination was most common (n=84, 21%). Most of the prescriptions were containing four drugs per prescriptions (n=130, 32.5%). Only 10% of the prescription was given by generic name and rest 90% were given by brand name. Oral dosage form of AMAs was predominant (n=340, 85%). Vitamins and supplement were most common comedication received by patients. Conclusion: Antibiotic use was found to be reasonable and rational in most of the cases. However, still, prescribers should improve prescribing practices and make it more rational.